Investigation into the value of Papanicolaou stained cervical smears for the diagnosis of chlamydial cervical infection. Issue 4 (April 1985) - Forster, G E; Cookey, I; Munday, P E; Richman, P I; Jha, R; Coleman, D; Thomas, B J; Hawkins, D A; Evans, R T; Taylor-Robinson, D
Abstract : Forty five (37%) of 121 female contacts of men with non-gonococcal urethritis or gonorrhoea were chlamydia positive, as judged by isolation or by detecting elementary bodies in smears with a fluorescein labelled chlamydial monoclonal antibody. Only six (13%) of these, however, had Papanicolaou stained smears in which there were inclusion like changes suggestive of chlamydial infection. Furthermore, of 15 patients who had such cytological changes, chlamydiae were detected in only six and the abnormalities were found also in Papanicolaou stained smears from 10 (13%) of the 76 chlamydia negative patients. Modifying the Papanicolaou stained smears by including endocervical material did not increase sensitivity. In addition, destaining and restaining them with the monoclonal antibody was time consuming and the results were unreliable. The staining of cervical smears with Papanicolaou reagent is a technique of low sensitivity and specificity for diagnosing or screening for chlamydial cervical infection and cannot be recommended.